A National Quality Initiative to Improve Palliative Care Outcomes: Identifying Enabling Factors that Drive Quality Improvement - Sabina Clapham; Katherine Clark; Kylie Draper; Fiorina Mastroianni; Jesse Rand; Lisa Redwood; David Currow (Palliative Medicine Reports)
Background: The Palliative Care Outcomes Collaboration (PCOC), established in 2005 and funded by the Australian Government, is a national quality improvement initiative that integrates patient outcome measures into routine clinical practice. While PCOC supports services to improve patient care, implementation across diverse clinical settings presents challenges, with variation observed between similarly resourced services. Engaging services in continuous quality improvement proves difficult as the program grows. Objectives: To identify factors associated with high-performing palliative care services and develop and evaluate an implementation framework and education program that supports continuous quality improvement. Methods: Patient outcome data and case studies from established PCOC-participating services were analyzed to identify high-performing services and the factors enabling successful integration of outcome measures. Based on the findings, an implementation framework was developed. Improvement trends were assessed in 20 services participating pre-intervention (2016–2018) and 11 services participating post-intervention (2022–2024). Results: Five key strategies and 25 enabling factors for successful integration were identified including, leadership and governance; education to improve data literacy; infrastructure for the meaningful management of data; and uptake of PCOC in quality systems. The post-intervention services started with higher benchmark performance and showed improvements within 6 months of implementation. Addressing patient’s psychological/spiritual needs continues to be challenging. Conclusion: Quality improvement involving outcome measurement and benchmarking in palliative care requires education and structured implementation with ongoing feedback. The PCOC initiative demonstrates that improving patient outcomes involves more than collecting and analyzing outcome measures and benchmarking—it requires integrated assessment models, education, and resources to support information-driven quality improvement.